Improving Scientific Literacy through Cooperative Learning: Eclipse Crossword for Students in the Border Area of Indonesia - Niken Eka Priyani (UIN Raden Mas Said Surakarta, 2022)
This study intends to improve students' scientific literacy through cooperative learning using EclipseCrossword from Rumah Belajar application developed by Pusdatin Kemdikbud. This Classroom Action Research (CAR) was carried out in two cycles. It involved 12 fourth-grade students at SDN 29 Idai, Sintang Regency, West Kalimantan, Indonesia. The stages of this research are planning, acting, observing, and reflecting. The results indicate that the students’ scientific literacy in Cycle I was 51%, categorized as ‘poor’. It was increased to 78%, categorized as ‘good’ in Cycle II. The increase in students’ scientific literacy was depicted in the aspect of applying scientific knowledge by 16%, concluding information based on analysis by 33%, analyzing information from each representation by 29%, and explaining the benefits of scientific knowledge for society by 24%. The increase in students’ scientific literacy in cooperative learning using EclipseCrossword proves its merits as an alternative learning model for schools located in the Frontier, Outermost, and Disadvantaged (3T) areas.